Novel evaluations of sources and sinks of dissolved oxygen via stable isotopes in lentic water bodies - Dordoni, Marlene; Seewald, Michael; Rinke, Karsten; Schmidmeier, Jakob; Barth, Johannes (Science of the Total Environment, 2022)
Dissolved oxygen (DO) dynamics of a temperate drinking water reservoir in the Harz Mountains (Germany) were investigated over a time period of 18 months. Via depth profiles in a fortnightly sampling resolution we were able to trace DO and temperature dynamics including the formation and breakdown of a Metalimnetic Oxygen Minimum (MOM) by means of DO concentration, saturation patterns and stable isotope ratios of dissolved oxygen (expressed as δ18ODO). Over the evaluation period, 19.4 % of the samples collected had δ18ODO values compatible with atmospheric equilibration (+24.6 ‰ ± 0.4 ‰). With values smaller and larger than this threshold, the remaining δ18ODO values showed that 40.8 % of our samples were dominated by photosynthesis and 39.8 % by respiration. From December to April the reservoir was mixed and DO consumption by respiration exceeded production via photosynthesis. During stratification period, quantification of respiration/photosynthesis rates (R/P) confirmed the epilimnion as a photosynthetic (i.e. net-autotrophic) environment while the hypolimnion was heterotrophic and dominated by respiration at various degrees. Samples of the MOM zone showed the highest R/P ratios and had among the most positive δ18ODO signals caused by respiration. This study showed that combinations of DO concentrations and their isotope ratios are promising to quantify critical zones of respiration and photosynthesis in aquatic environments.
CRIS-Team Scopus Importer:2022-07-01
Keywords: Atmospheric influence; Lentic water bodies; Metalimnetic Oxygen Minimum (MOM); Photosynthesis; R/P ratios; Respiration